Nivel de cumplimiento de la lista de verificación de seguridad de la cirugía en un hospital del Minsa de Chimbote - Camacho Rodríguez, Anthony Luis (2023)
This research is a quantitative, descriptive, cross-sectional approach, aimed at determining the level of compliance with the Surgery Safety Checklist at the Eleazar Guzmán Barrón Regional Hospital, Chimbote. We worked with 19 nurses. The data were obtained through two instruments: a questionnaire "level of compliance with the checklist of surgery insurance" and an observation guide through a checklist. The data were processed in the SPSS V25.0 program, the results were presented in tables: 68.4% of nurses have a regular compliance level and 21.1% a good compliance level, in the first dimension: Entry 78.9% of nurses have a good level of compliance and 21.1% have a level of regular compliance; In the second dimension: Surgical pause 68.4% of nurses have a bad level of compliance, 26.3% have a level of regular compliance while 5.3% have a bad level of compliance; In the third dimension: Exit 68.4% of nurses have a good level of compliance while 31.6% have a level of regular compliance